A review of organic waste enrichment for inducing palatability of black soldier fly larvae: Wastes to valuable resources - Raksasat, R. (Elsevier Ltd, 2020)
The increase of annual organic wastes generated worldwide has become a major problem for many countries since the mismanagement could bring about negative effects on the environment besides, being costly for an innocuous disposal. Recently, insect larvae have been investigated to valorize organic wastes. This entomoremediation approach is rising from the ability of the insect larvae to convert organic wastes into its biomass via assimilation process as catapulted by the natural demand to complete its lifecycle. Among the insect species, black soldier fly or Hermetia illucens is widely researched since the larvae can grow in various environments while being saprophagous in nature. Even though black soldier fly larvae (BSFL) can ingest various decay materials, some organic wastes such as sewage sludge or lignocellulosic wastes such as waste coconut endosperm are destitute of decent nutrients that could retard the BSFL growth. Hence, blending with nutrient-rich low-cost substrates such as palm kernel expeller, soybean curd residue, etc. is employed to fortify the nutritional contents of larval feeding substrates prior to administering to the BSFL. Alternatively, microbial fermentation can be adopted to breakdown the lignocellulosic wastes, exuding essential nutrients for growing BSFL. Upon reaching maturity, the BSFL can be harvested to serve as the protein and lipid feedstock. The larval protein can be made into insect meal for farmed animals, whilst the lipid source could be extracted and transesterified into larval biodiesel to cushion the global energy demands. Henceforth, this review presents the influence of various organic wastes introduced to feed BSFL, targeting to reduce wastes and producing biochemicals from mature larvae through entomoremediation. Modification of recalcitrant organic wastes via fermentation processes is also unveiled to ameliorate the BSFL growth. Lastly, the sustainable applications of harvested BSFL biomass are as well covered together with the immediate shortcomings that entail further researches. Â© 2020 Elsevier Ltd